2020
DOI: 10.3390/ph13080166
|View full text |Cite
|
Sign up to set email alerts
|

Immune Pathogenesis of COVID-19 Intoxication: Storm or Silence?

Abstract: Dysregulation of the immune system undoubtedly plays an important and, perhaps, determining role in the COVID-19 pathogenesis. While the main treatment of the COVID-19 intoxication is focused on neutralizing the excessive inflammatory response, it is worth considering an equally significant problem of the immunosuppressive conditions including immuno-paralysis, which lead to the secondary infection. Therefore, choosing a treatment strategy for the immune-mediated complications of coronavirus infection, one has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 116 publications
0
10
0
7
Order By: Relevance
“…Finally, human coronavirus can lie dormant in the leukocytes for a long period and may manifest as delayed or persistent central nervous system infection, later giving rise to movement disorders 87 . Indeed, immune dysregulation brought about by SARS‐CoV‐2 infection 88 may lead to neurodegeneration 89 and potentially neurodegenerative movement disorders might manifest later. Notwithstanding, movement disorders are being increasingly documented because of the higher reporting frequency of COVID‐19 cases worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, human coronavirus can lie dormant in the leukocytes for a long period and may manifest as delayed or persistent central nervous system infection, later giving rise to movement disorders 87 . Indeed, immune dysregulation brought about by SARS‐CoV‐2 infection 88 may lead to neurodegeneration 89 and potentially neurodegenerative movement disorders might manifest later. Notwithstanding, movement disorders are being increasingly documented because of the higher reporting frequency of COVID‐19 cases worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed nonhuman RNA presence within each sample using KRAKEN2 tools and a database of thousands of transcriptomes from bacteria/plants/viruses/fungi. Three patients (13,28,36) have higher values of mapped bacterial RNA, four (12,14,18,25,28) with higher plant RNA, and two (27 and 25) with high viral RNA (Figure 6A). Multiple patients carried elevation of bacterial species such as Photobacterium 6B).…”
Section: Secondary Infectionsmentioning
confidence: 99%
“…In choosing the right treatment strategy for the immunemediated complications of coronavirus infection, neutralizing the "cytokine storm" is often the putative goal. Still, it is vital to recognize immune incompetence that turns into immunoparalysis with increased vulnerability to secondary infections (14). In addition to acute complications, the global activation of the immune system may be related to poorly understood chronic problems in survivors of COVID-19 (15,16) that are beginning to surface in COVID-19 "long-haulers."…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that patients with severe COVID-19 have acute lymphopenia and damage to lymphatic tissues such as the spleen and lymph nodes, leading to immune paralysis that interferes with the clearance of virus [ 49 ]. The enhanced ratio of neutrophils to lymphocytes was observed in severe COVID-19 patients with lymphopenia, which is considered a clear sign of systemic inflammation and poor prognosis [ 50 ]. In COVID-19 patients, the T cell and NK cell counts are reduced, and significantly lower in the critically ill cases [ 51 53 ].…”
Section: Cytokine Storm Accounts For the Severity Of Covid-19mentioning
confidence: 99%